Target capturing in an ellipsoidal region for a swarm of double integrator agents - GAZİ, VEYSEL (My University, 2022)
In this paper we focus on the target capturing problem for a swarm of agents modelled as double integrators in any finite space dimension. Each agent knows the relative position of the target and has only an estimation of its velocity and acceleration. Given that the estimation errors are bounded by some known values, it is possible to design a control law that ensures that agents enter a user-defined ellipsoidal ring around the moving target. Agents know the relative position of the other members whose distance is smaller than a common detection radius. Finally, in the case of no uncertainty about target data and homogeneous agents, we show how the swarm can reach a static configuration around the moving target. Some simulations are reported to show the effectiveness of the proposed strategy.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Engineering and Technology; OTOMASYON & KONTROL SİSTEMLERİ; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); AUTOMATION & CONTROL SYSTEMS; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Mühendislik (çeşitli); Kontrol ve Optimizasyon; Fizik Bilimleri; General Engineering; Engineering (miscellaneous); Control and Systems Engineering; Control and Optimization; Physical Sciences; Agents-based systems; cooperative control; swarms; target-capturing; CIRCUMNAVIGATION; LOCALIZATION; Agents-based systems; cooperative control; swarms; target-capturing